Thiruvaran, T., Ambikairajah, E., & Epps, J. (2008). FM features for automatic forensic speaker recognition. In Ninth Annual Conference of the International Speech Communication Association. - Thiruvaran, T.; Ambikairajah, E.; Epps, J. (My University, 2008)
Frequency modulation (FM) information from the speech signal is herein proposed to complement the conventional amplitude based features for automatic forensic speaker recognition systems. In addition to presenting the AM-FM model of speech used to generate the proposed frequency modulation features, the significance of frequency modulation for speaker recognition is discussed. Evaluation results from an automatic forensic speaker recognition system combining FM and MFCC features are shown to out-perform those of a system employing MFCC features alone, in terms of all typical metrics, such as detection error trade-off curves, Tippett curves and applied probability of error curves.
Keywords: frequency modulation; automatic forensic speaker recognition